The new frontier of age limits, or youthoods among the Meru (Kenya) - Anne-Marie Peatrik (Ateliers d'Anthropologie)
In the much-changed context of the present-day lives of the Tigania-Igembe Meru (agro-herders living north-east of Mount Kenya who once had a political generation-set system), the article examines the differentiation of categories of youth and the modalities of age limits. Contrary to common perceptions, the transition to the next grade was neither automatic nor devoid of strong tensions, and youth was something other than that intermediate phase between childhood and adulthood, as the society and culture under consideration testifies to, through narratives, rules and a special vocabulary for the purpose. Nowadays, under the effect of widespread schooling, new youth classifications have appeared, overlapping or replacing old ones. The still-significant key question of initiations has shifted, causing a major de-synchronisation between the paths of girls and boys. The article offers a contribution to an anthropology of youth, viewed here from the perspective of its limits, and aims to put the rite of passage back in its rightful place within processes that concern both complex trajectories and the crucial junctions of existence.